The Development of Islamic Psychospiritual Scale for Drug Addicts - Sa'ari, Che Zarrina; Zainal Abidin, Mohd Syukri; Hj. Ahmad, Siti Sarah; Syed Abdul Rahman, Syed Mohammad Hilmi; Che Nordin, Mohd Khairul Naim; Syed Muhsin, Sharifah Basirah; Mohd Akib, Mohd Manawi (Afkar: Jurnal Akidah dan Pemikiran Islam, 2020)
The increase in the percentage of drug addiction every year is of great concern to society and the country. However, there is no denying that various parties such as government agencies, non-governmental organizations, private agencies and even individuals, each have played various roles in helping the government deal with this drug addiction problem. Academics, psychologists, counsellors and Islamic psychospiritual therapists are among those who contributed to this issue from theoretical and contextual aspects, including in the development of scale-based assessment instruments to drug addicts. Past studies explained that there is a close link between spiritual aridity and drug addiction. Recognizing the spiritual need to address drug addiction, this article discusses the Islamic Psychospiritual Scale (ZATIP) instrument for drug addicts to help researchers measure the addicts’ spiritual level and condition. This instrument is developed through a phase of validity and reliability employing two methods, first, expert verification using interview method and thematic qualitative analysis; and method of questionnaire on Content Validity Index (CVI) and statistical analysis. The second method involved a pilot test of the instrument on 25 drug addicts and applying statistical analysis. The results of the study found that the Islamic Psychospiritual Scale (ZATIP) instrument has a high value of validity and reliability and is suitable for use in assessing the spiritual level of individuals, especially drug addicts.